The Effects Induced by a Specific Program on the Development of Segmental Flexibility in Athletes Aged 7-14 in Synchronized Swimming - Adela Badau; Barna Szabo-Csifo; Laura Ciulea; Razvan Alexandrescu; Dana Badau (MDPI AG, 2021)
This research aims to expand the knowledge on the level of development of segmental flexibility, to girls aged 7-14 years, who practice synchronized swimming. The study includes 112 girls aged between 7 and 14 years, divided into groups on age, every two years, and on the period of synchronized swimming between 6 months and 42 months. The study focused on three body segments, namely: torso, hip, and shoulder. Segmental flexibility was assessed using 5 tests: standing trunk flexion, shoulder flexibility, Hip-split legs sideways, Hip-split antero-posterior with the right foot forward, and Hip-split antero-posterior with the left foot forward, performed in the gym. The statistical analysis was performed using the SPSS-24 software aiming at the following parameters: arithmetic means (X), standard deviation (SD), minimum (Min), maximum (Max), CI-95% Confidence Interval for Mean with the two lower and upper marks, Kolmogorov-Smirnov test for testing the normality of data distribution and a multifactor ANOVA analysis, using the F test. The most significant improvements highlighted by the differences between initial and final were for: the shoulder flexibility test in the 13-14 years' groups; flexibility of the spine registered the biggest difference between the 9-10 years' group; for hip-split legs sideways the biggest difference was between 9-10 years' group and 13-14 years and 9-10 years, too. The hip-split antero-posterior tests with the left and also, for right foot forward, showed the biggest differences between tests for 13-14 age groups. The development of joint flexibility has an upward evolution, being conditioned by the age of the practitioners and by the operating methodology specific to synchronized swimming. The longer the training period, the greater the premises for the development of segmental flexibility.